Fermentation by Eco Enzyme on Nutritional Content of Rice Straw, Corn Straw, and Oil Palm Fronds - Ervinta Ervinta; Hasnudi; R. Edhy Mirwandhono; N Ginting; B Simanullang (Talenta Publisher, 2020)
The low nutrient content of agricultural waste is an obstacle to use as feed. The addition of eco enzyme as biological activators can help the fermentation process. The aim of this research was to determine the effect of three doses of eco enzyme as a starter fermentation of rice straw, corn straw, and palm fronds on changes in the nutritional content of 21 days fermentation. This study used a completely randomized design method with two factorial (three treatments and three replications). Factor D: Doses (D1 = 1%; D2 = 3%; D3 = 5%) and factor L: Forage (L1 = rice straw; L2 = corn straw; L3 = oil palm fronds). The parameters studied were moisture content (MC), dry matter (DM), crude protein (CP), crude fiber (CF). The results of this research showed that addition of eco enzyme dose of 5% on L1, 3% on L2 and 3% L3 can increased water content and crude protein, and reduce levels of dry matter and crude fiber of forage compared without fermentation.